Potentiostatic deposition of DNA for scanning probe microscopy. - Lindsay, S M (1992)
We describe a procedure for reversible adsorption of DNA onto a gold electrode maintained under potential control. The adsorbate can be imaged by scanning probe microscopy in situ. Quantitative control of a molecular adsorbate for microscopy is now possible. We found a potential window (between 0 and 180 mV versus a silver wire quasi reference) over which a gold (111) surface under phosphate buffer is positively charged, but is not covered with a dense adsorbate. When DNA is present in these conditions, molecules adsorb onto the electrode and remain stable under repeated scanning with a scanning tunneling microscope (STM). They become removed when the surface is brought to a negative charge. When operated at tunnel currents below approximately 0.4 nA, the STM yields a resolution of approximately 1 nm, which is better than can be obtained with atomic force microscopy (AFM) at present. We illustrate this procedure by imaging a series of DNA molecules made by ligating a 21 base-pair oligonucleotide. We observed the expected series of fragment lengths but small fragments are adsorbed preferentially.